2022
DOI: 10.3390/nano12162850
|View full text |Cite
|
Sign up to set email alerts
|

Co3O4 Nanopetals Grown on the Porous CuO Network for the Photocatalytic Degradation

Abstract: Designing a novel photocatalytic composite for the efficient degradation of organic dyes remains a serious challenge. Herein, the multi-layered Co3O4@NP−CuO photocatalyst with unique features, i.e., the self-supporting, hierarchical porous network as well as the construction of heterojunction between Co3O4 and CuO, are synthesized by dealloying-electrodeposition and subsequent thermal treatment techniques. It is found that the interwoven ultrathin Co3O4 nanopetals evenly grow on the nanoporous CuO network (Co3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…In detail, the Co 3 O 4 layer on top has a nanopetal structure that is intertwined and developed uniformly on the ZnO substrate, similar to previous reports on electrochemically deposited Co 3 O 4 . 37 Thus, based on the SEM images of the samples, it can be concluded that the Co 3 O 4 /ZnO bilayer material with a nanopetal/nanoplate structure on the FTO substrate was successfully synthesized by the electrochemical deposition method with high coverage and uniformity.…”
Section: Resultsmentioning
confidence: 95%
“…In detail, the Co 3 O 4 layer on top has a nanopetal structure that is intertwined and developed uniformly on the ZnO substrate, similar to previous reports on electrochemically deposited Co 3 O 4 . 37 Thus, based on the SEM images of the samples, it can be concluded that the Co 3 O 4 /ZnO bilayer material with a nanopetal/nanoplate structure on the FTO substrate was successfully synthesized by the electrochemical deposition method with high coverage and uniformity.…”
Section: Resultsmentioning
confidence: 95%
“…20 Based on the above discussion, we expect that CuO/Co 3 O 4 heterojunction nanomaterials can have good electrocatalytic methanol oxidation performance. Considering the wide application of heterojunction structure in the field of photocatalysis, Sun et al 21 have designed a Co 3 O 4 @NP-CuO composite, which exhibits excellent photodegradation performance against RhB. Zhang et al 22 have synthesized a CuO/Co 3 O 4 hollow polyhedral nanocage composite, which improves the photocatalytic performance of water oxidation and has excellent stability.…”
Section: Introductionmentioning
confidence: 99%